PENGAWASAN KUALITAS AIR BERSIH OLEH DINAS KESEHATAN KOTA PEKANBARU (STUDI KASUS DI KECAMATAN RUMBAI PESISIR TAHUN 2013) - Mhd Sony Septyan; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Clean water is a source of survival for the whole society on the face of the earth. Therefore, monitoring of water contained in the Act of 1945, Article 33, paragraph 3 states that: